Analisis Sistem Keberangkatan Calon Jamaah Haji Menggunakan Metode Weighted Product - Fredricka, Jhoanne; Ihsan, Muhammad Fikri (UNIVED Press, 2020)
The Hajj pilgrimage is carried out based on the principles of justice, professionalism and accountability so that Hajj pilgrims can carry out their worship in accordance with the provisions of Islamic teachings. The Ministry of Religion of Bengkulu Province has used an information system in processing data on departure schedules for prospective Hajj pilgrims, however, determining the estimated departure schedule is still done manually. This research aims to analyze the departure schedule of prospective Hajj pilgrims using the weighted product method. The weighted product method in processing departure data is carried out by determining criteria, namely the age of the pilgrims, history of the Hajj and length of registration based on normalized weight calculations and determining vector values, so that a ranking is obtained where the highest value is taken which is used as the main priority.